KONSTRUKSI SOSIAL TEKNOLOGI DALAM PEMBELAJARAN VIRTUAL DI KOTA TANGERANG - Nurhalidah Nurhalidah; Rizki Briandana (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
This study was conducted to determine how communication process of Social Construction of Technology (SCOT) and communication disorders in virtual learning at SMK Nusantara 1 Kota Tangerang during COVID-19 Pandemic. Study technology in the context of social science is about the meaning of technology for students and teachers and how they respond to, and adapt to, the presence of technology. This study uses case study methods. The data collection techniques used were observation and in-depth interview. Purposive sampling method was used to take samples and for data analysis using the Miles and Huberman interactive analysis model. The result shows that an implementation of virtual learning activities at SMK Nusantara 1 Kota Tangerang applies SCOT in the formation of social technology to explore forms of virtual learning during COVID 19 pandemic. SCOT means that technology is not determined by technology design but there is an interaction between technology and its users. namely teachers and students. Thus, the desired instructional outcomes are created. However, the availability of the internet and problematic communication media have also become a nuisance in virtual learning.